MANAGEMENT OF REMOVABLE DENTURES WITH FEW REMAINING TEETH - Arifianti, Isti; Nabiila Suharto, Alyaa (Fakultas Kedokteran Gigi Unjani, 2024)
Tooth loss is the most common cause of decreased masticatory function. Losing teeth can also affect the oral cavity and general health, affecting a person's overall quality of life. Various things can cause tooth loss. The most common cause of tooth loss is poor oral health, especially caries and periodontal disease. Dentures can be made for patients who have lost all their teeth or have some remaining teeth. Retaining the remaining natural teeth can inhibit the alveolar bone resorption process and maintain bone height, thereby increasing the retention and stability of the denture. A 60-year-old female patient complained that many teeth were missing due to upper and lower jaw extraction, making it uncomfortable when eating and talking. The upper jaw has teeth 11, 21, 22, and 23 remaining, and the lower jaw still has 43 remain. The patient will have a removable denture with teeth 11, 23, and 43 as supporting teeth. The presence of a tooth can prevent alveolar bone resorption, especially if there is an occlusion load directly on the alveolar bone in edentulous cases. Natural teeth as supports can slow alveolar bone resorption and maintain retention and stabilization of dentures. DOI : 10.54052/jhds.v3n3.p263-272